Mungkin Kita Sudah Sampai di Sana: Mengamati Kekuasaan Melalui Dunia Distopia Postmodernis dalam The Ballad of Songbirds and Snakes (2023) - Maulida, Aisyah Caesarani; Ariastuti, Marti Fauziah (Sanata Dharma University, 2025)
Movies are more than just works of art and fiction. Oftentimes, motion pictures portray, allude, and satirize social phenomena. This paper observes control mechanisms used by the government in Suzanne Collins’ book adaptation movie The Ballad of Songbirds and Snakes (2023) to assert power over citizens. By analyzing selected movie scenes and dialogue related to power relations through textual and visual analysis, the study reveals parallelism of dystopian elements shown in the movie with current sociopolitical situation through Foucault’s postmodernist view on power. The findings show that government in The Ballad of Songbirds and Snakes creates and utilizes citizens’ internalized discipline through surveillance to establish power within them as docile bodies, echoing how subtle power is used by governments across the world to cultivate public orderliness in the modern days.